Penglibatan Ketenteraan Saljuq Era Alp Arslan (1063-1072) Dalam Perang Manzikert (1071) - Raja Muhammad Imran Raja Abdul Aziz; Ezad Azraai Jamsari; Adibah Sulaiman; Noorsafuan Che Noh (Penerbit Universiti Islam Melaka, 2024)
Indexed by MyCite